KUALITAS STANDAR PELAPORAN KEUANGAN, AUDITING DI DALAM HUBUNGAN KEMAJUAN PASAR MODAL DAN PEREKONOMIAN NEGARA - Ramdani, Rahmat Fajar; Sisdianto, Ersi; Darmayanti, Elmira Febri (Universitas Muhammadiyah Magelang, 2019)
The purpose of this research is to test moderate effect financial reporting and auditing standard quality between corelation of capital market development and economic development. This research used 57 countries as sampel with three years observation started from 2015 to 2017. This research use index score quality from world economic forum as measurement of financial reporting dan auditing standard quality, to measure capital market and economic development this research used acumulation market capitalization stock in year and product domestic bruto as measurement. To analysis hyphotesis of this research used Moderated Regression Analysis (MRA) approach. The result from this research showed the quality of financial reporting and auditing in country did not have moderated effect between corelation of capital market development and economic development this happened because audited financial report is only tool for decision making used by investor and not have direct effect in economic sector rill. Keyword :financial reporting and auditing standard quality, capital market development, economic